Temporal partitioning of diurnal bird and nocturnal small mammal visitors to a winter flowering endemic succulent. Issue 2 (3rd April 2021) - Payne, Stephanie L; Symes, Craig T; Witkowski, Ed TF
Abstract : Floral nectar is an important attractant and reward for visitors, and is often produced in synchrony with peak activity of pollinators. Aloe peglerae flowers in winter, and previous studies have shown that it is pollinated primarily by diurnal generalist birds, with small mammals making additional contributions to pollination at night. Nectar produced during the day is the main attractant and reward for birds, but the nectar rewards available to small mammals are unknown. This paper investigates nectar availability in Aloe peglerae, because small mammals may be feeding on remaining, or freshly produced, nectar at night. Nectar availability over a 24-hour period was measured in screened and unscreened plants ( n = ten plants per treatment), and the associated partitioning of visits by diurnal birds and nocturnal small mammals assessed. Nectar is constantly available over 24-hours, but in different quantities. Nectar volume of screened (nectar availability) and unscreened (standing crop) plants, is significantly higher early in the morning after sunrise, compared with all other sampling periods during the 24-hour period. Nectar concentration did not vary over 24-hours, averaging 11.5 ± 0.4% w/w (unscreened) across the entire 24-hour period. Peaks in visits by different guilds occurred at periods (i.e. diurnal birds and nocturnal small mammals) when nectar availability was high. Aloe peglerae has higher daytime nectar production, when its primary pollinators are most active, but the continual, albeit reduced, nectar availability at night attracts small mammals. Mobile diurnal birds, and less-mobile nocturnal small mammals, both rely on this nectar resource during dry and cold South African winters and, in turn, are important pollinators for this Critically Endangered Aloe species.